(untitled) (La Lupa. Colección fueguina de divulgación científica, 2023)
COMITÉ EDITORIAL Editoras responsables Jimena Elizabeth Chaves Paula Rodríguez Editores asistentes Lu Denisse Chiberry Cecilia Inés Gutiérrez Natalia Garces Cuartas María Constanza Maluendez Testoni Victoria Mosqueira González Facundo Sota Asesores informáticos Fernando Gini Rodrigo Leandro Gauna Diseño y Diagramación Irina Castro Peña Ushuaia, Tierra del Fuego, Argentina Instagram: @hello.irina.dg Impresión M&A Diseño y Comunicación S.R.L. Buenos Aires, Argentina E-mail: info@myaweb.com.ar